ISLAMIC SPIRITUAL CAPITAL IMPLEMENTATION OF INDONESIAN MIGRANT WORKERS FROM MADURA - Kurniasari, Widita; Titik, Crisanty Sutristyaningtyas; Muafi, Muafi; Muhdianto, Ahmad; Hasanah, Nabilatul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
The purpose of this research is to obtain an in-depth picture of the implementation of Islamic spiritual capital in the practices of Indonesian migrant workers from Madura. The approach used in this research is Islamic phenomenology. This research explores the event/phenomenon of Indonesian Migrant Workers originating from Madura. This method helps reveal how Islamic spiritual capital is implemented in the practices of Indonesian Migrant Workers from Madura. The results of the research show that the Islamic spiritual capital possessed by Indonesian Migrant Workers from Madura has not been practiced thoroughly (kaffah). Islamic spiritual capital which is reflected in work ethic, work motivation and professional governance has not yet become a guide for Indonesian Migrant Workers. Even though these Indonesian Migrant Workers from Madura have a work ethic, namely working hard, they ignore the applicable rules, namely becoming illegal migrant workers. Their main motivation for working is only to get a higher income so that their goal of working is only for worldly matters. The management of official Indonesian Migrant Workers from Madura is in accordance with procedures. Even though the Indonesian Government through the Ministry of Manpower has regulated the flow of registration for the placement of Indonesian migrant workers through an online system, there is still the practice of brokering Indonesian Migrant Workers which is difficult to eradicate.